Factors influencing the adoption of e-banking in Somalia - Mohamed, Mohamed Ismail (2018)
Electronic banking concept has been in practice worldwide especially in the developed nations compared to developing countries in which Somalia is no exception to this trend. The purpose of this study is to identify the factors that determine e-banking adoption in Somalia. Since the introduction of e-banking, several studies have explored diverse issues of e-banking concept in the developing nations. This study identified four main determinants of e-banking adoption which includes internet speed, trust, perceive ease of use, and perceive usefulness. The findings of this study show that internet speed, trust, perceived ease of use and perceived usefulness played a significant role in determining e-banking adoption. The method employed in this study involved primary data through online survey questionnaire. The limitation of the study is basically a quantitative research; hence future research should include other geographical areas such as other cities in Somalia meeting the generalization of the findings. Also, this study suggests that future research should implement a longitudinal study where recurring measurement on respondents is done, thereby understanding the behaviour of the e-banking adoption over time.